Differential stimulation of phosphorus-mobilizing bacteria by common bean genotypes in Amazonian Dark Earth and Agricultural Soils with varying fertility levels - Fonseca, Mariley; Pedrinho, Alexandre; Merloti, Luis Fernando; Bossolani, João William [UNESP]; Lemos, Leandro Nascimento; Martins e Martins, Mayara; Mendes, Lucas William; Mui, Tsai Siu (Elsevier, 2025)
Phosphorus (P) is an essential element for plant metabolism and often limits agricultural production due to its strong immobilization in soils. Microbial activity plays a crucial role in nutrient cycling, particularly in mobilizing P for plant uptake. This study evaluated how plants with different P use efficiencies influence the structure, diversity, and composition of the microbial community, with a focus on P-mobilizing bacteria, in soils with varying fertility levels. We hypothesized that plants with contrasting P use efficiencies differentially recruit rhizosphere microbiota associated with the P cycle. To test this hypothesis, a greenhouse experiment was conducted using two common bean (Phaseolus vulgaris L.) genotypes, BAT 477 (G1) and DOR 364 (G2), known for their contrasting P assimilation efficiencies. The common beans were grown in Amazonian Dark Earth (ADE) and agricultural soil (AS) until the pre-flowering phenological stage (R5). Rhizosphere and bulk soil (BS) samples were collected for microbiological, enzymatic, and P fractionation analyses. Amplicon sequencing revealed that the composition and relative abundance of the prokaryotic community were significantly influenced by the common bean genotypes across the different soil types. Acid phosphatase activity was approximately 22% higher in the rhizosphere than in BS for both genotypes, irrespective of soil type. Alkaline phosphatase activity, however, exhibited distinct patterns: in ADE, G1 showed 48% higher activity than BS, while in AS, G2 displayed the highest activity, with a 33.6% increase compared to BS. Redundancy analysis (RDA) in ADE revealed three distinct clusters (G1 ≠ G2 ≠ BS), indicating genotype-specific microbial recruitment patterns with significant positive correlations to the moderately labile P fraction. In AS, only two clusters were observed (G1+G2 and BS), with positive correlations to the moderately labile P fraction but no distinction between genotypes. These findings demonstrate that plants with differing P assimilation efficiencies distinctly modulate the rhizosphere microbiome, influencing P mobilization in a soil fertility-dependent manner. This study highlights the potential of leveraging plant-microbe interactions to enhance P cycling and utilization in agricultural systems, paving the way for more sustainable and efficient crop production practices.
Keywords: Enzymatic activity; Microbial activity; Microbial community; Rhizosphere microbiome